2017
DOI: 10.5755/j01.ms.23.3.17640
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance of Sintered Composite Hardfacings under Different Abrasive Wear Conditions

Abstract: The article focuses on vacuum liquid phase sintered (PM) composite hardfacings and their behaviour under different abrasive wear conditions. Hardfacings studied contained 30 -50 vol % fine, coarse or multimodal (fine and coarse) hardmetal reinforcement. For wear resistance studies, we used the Abrasive Rubber Wheel Wear (ARWW) test as a threebody abrasive wear test, the Abrasive Wheel Wear (AWW) test as a two-body abrasive wear test and the Abrasive-Impact Erosion wear (AIEW) test as an abrasive-erosive wear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As the carrier of erodent particles, the liquid medium could infiltrate into the rubber during erosion process, causing the dynamic swelling of rubber, which will make the rubber aged and further affected the tribological properties [24,25]. The investigations of Lv et al [16,19] showed that after swelling, the wear performance of NBR reduced, the hardness decreased, and the surface damage became more serious. Ch'ng [25] reported that the amount of swelling of rubber in solvent is affected by loading.…”
Section: Interaction Between Swelling and Erosionmentioning
confidence: 99%
“…As the carrier of erodent particles, the liquid medium could infiltrate into the rubber during erosion process, causing the dynamic swelling of rubber, which will make the rubber aged and further affected the tribological properties [24,25]. The investigations of Lv et al [16,19] showed that after swelling, the wear performance of NBR reduced, the hardness decreased, and the surface damage became more serious. Ch'ng [25] reported that the amount of swelling of rubber in solvent is affected by loading.…”
Section: Interaction Between Swelling and Erosionmentioning
confidence: 99%
“…where 𝛼𝛼′ 𝜀𝜀 𝑐𝑐 2 is a dimensionless ratio, taken from [10]; ρ 1 is the density of the target material [mg/mm 3 ]; H dynamic is the dynamic hardness of the target material [N/mm 2 ]; HV1 was used for calculations [11].…”
Section: Used Mathematical Modelsmentioning
confidence: 99%